Źródła mądrości filozofów - Drozdowicz, Zbigniew (Bydgoski Oddział Polskiego Towarzystwa Filozoficznego Filo-Sofija, 2014)
The Sources of Philosophical Wisdom In these remarks I ponder the question of the sources of philosophical wisdom: the ancient as well as the contemporary one. I seek the answer to this question by recalling those philosophers who not only gave evidence of their wisdom but also indicated its origins. In the summary, I formulate conclusions in regard to both the authenticity of these sources and the credibility of those indications and their cognitive value. The most general conclusion formulated by me might be summed up by the remark that in philosophy (and not only in philosophy) we should be wise with the wisdom of others, but also our own: however, in such situations our thinking is creative in character. Keywords: philosophical wisdom, great masters of philosophical thought, fashionable philosophers.
Keywords: philosophical wisdom; great masters of philosophical thought; fashionable philosophers